Proactive response to tackle the threat of emerging drugs: Synthesis and toxicity evaluation of new cathinones. (September 2018) - Gaspar, Helena; Bronze, Soraia; Oliveira, Catarina; Victor, Bruno L.; Machuqueiro, Miguel; Pacheco, Rita; Caldeira, Maria João; Santos, Susana
Highlights: Twenty-one psychoactive cathinones, four of them new, were synthesized. Analytical data (NMR, GC–MS and HRESI-MS) for all cathinones were reported. The toxicity was assessed in HepG2 cells, with 3, 4-DMMC displaying the lowest EC50. Cytotoxicity depends on the acyl chain length and the aromatic ring substitution. MD simulations highlight how easily cathinones permeate lipid bilayers. Abstract: The emergence of potentially dangerous new psychoactive substances (NPS) imposes enormous challenges on forensic laboratories regarding their rapid and unambiguous identification. Access to comprehensive databases is essential for a quick characterization of these substances, allowing them to be categorized according to national and international legislations. In this work, it is reported the synthesis and structural characterization by NMR and MS of a library encompassing 21 cathinones, 4 of which are not yet reported in the literature, but with structural characteristics that make them a target for clandestine laboratories. This in-house library will be an important tool accessible to forensic laboratories, for the quick identification of seized NPS. The in vitro cytotoxicity of all cathinones was assessed in HepG2 cells, to have a preliminary but effective indication of their human hepatotoxicity potential. The two new cathinones DMB (8 ) and DMP (9 ) were the more cytotoxic, followed by the already seized mephedrone (2 ), 3, 4-DMMC (3 ), 4-MDMC (7 ), NEB (12 ) with EC50 values ranging from 0.81 mM for (3 ) to 1.28 mM for (2 ). Results suggest an increase of cytotoxicity with the increase of the chain length of the acyl moiety and with the substitution (with one or two methyl groups) in the aromatic ring. The nature of the amine moiety seems to play only a minor role in the cytotoxic effect. Molecular dynamics simulations were performed to evaluate the molecular details related with the observed cytotoxicities. Although these studies indicated that cathinones are able to cross lipid bilayers with relative ease, when in their neutral forms, it was observed only a partial correlation between lipophilicity and cytotoxicity, indicating that membrane trafficking may not be the only key factor influencing the bioactivity of these compounds. This work is a valuable contribution to the forensic science field since a quick identification of novel cathinones is urgent to match their rapid increase in the market.